Trade Off Antara Pengangguran, Inflasi, dan Kebijakan Pemerintah dalam Perspektif Islam - Irdlin Hanifah; Putri Kharisma Ayuningtiyas; Ines Kiki Faradila Hardika Dini; Lailatul Fadilah; Amalia Nuril Hidayati (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This research aims to analyze the trade-off between unemployment and inflation, as well as government policies from an Islamic perspective. Inflation and unemployment issues remain primary challenges for governments in maintaining economic stability. Unlike conventional economic perspectives that accept the trade-off between these two variables, Islamic economics offers a more integrative and holistic approach. Using a literature review method, this study analyzes various literature related to the relationship between unemployment and inflation from both conventional and Islamic economic perspectives. Research findings reveal that in conventional economics, the Phillips Curve depicts a trade-off between unemployment and inflation in the short term, though its validity is questioned in the long term. In contrast, from an Islamic economic perspective, there is no dichotomy between reducing unemployment and controlling inflation, as both can be addressed simultaneously through a just economic system aligned with Sharia principles. Islamic economics offers solutions through strengthening the real sector, profit-sharing financial systems, and implementing zakat, infaq, and waqf instruments that can create employment without generating inflationary pressures. This research provides insights into government policies that align with Sharia values in addressing current macroeconomic challenges.